2006
DOI: 10.1590/s1413-78522006000500009
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos das células tronco adultas de medula óssea e do plasma rico em plaquetas na regeneração e recuperação funcional nervosa em um modelo de defeito agudo em nervo perfiférico em rato

Abstract: OBJETIVOS: Foram avaliados os efeitos do uso de células tronco da medula óssea (CTM) e do plasma rico em plaquetas (PRP) na regeneração de nervos periféricos, utilizando um modelo estabelecido de regeneração de nervo ciático em ratos. MÉTODOS: Um defeito nervoso de 10 mm foi reconstruído com a utilização de um tubo de silicone preenchido com CTM, PRP ou ambos. O grupo controle recebeu somente o tubo de silicone. Foi realizado ainda um quinto grupo no qual o intervalo foi reconstruído utilizando o segmento ress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…The post‐operative period used in this research was 12 weeks, suggesting that the nerve fibers haven't reached complete regenerative development, with the myelinization process still incomplete. The observation period of 12 weeks employed in this study, the same observation period of Braga‐silva et al and Gravvanis et al, appears to be insufficient for axonal maturation and growth. However, nerve fiber myelination is merely a maturity signal, allowing these fibers to conduct nerve impulses before complete myelination.…”
Section: Discussionsupporting
confidence: 52%
“…The post‐operative period used in this research was 12 weeks, suggesting that the nerve fibers haven't reached complete regenerative development, with the myelinization process still incomplete. The observation period of 12 weeks employed in this study, the same observation period of Braga‐silva et al and Gravvanis et al, appears to be insufficient for axonal maturation and growth. However, nerve fiber myelination is merely a maturity signal, allowing these fibers to conduct nerve impulses before complete myelination.…”
Section: Discussionsupporting
confidence: 52%
“…Other studies using stem cells removed from bone marrow in different experimental models of peripheral nerve injury observed better results in the group that used stem cells compared to the other groups to improve gait function 26 , 27 , greater number of regenerated axons or myelinated fibers 26 , 27 , 36 , faster regenerative process 26 , 36 , 38 , less muscle loss 27 , greater myelin area 36 and less Wallerian degeneration 38 . In a meta-analysis study on the use of stem cells in the regeneration of peripheral nerve defects, the regenerative effect of stem cells was demonstrated mainly by analysis of the mass of the muscles studied, electrophysiological tests and gait tests 34 .…”
Section: Discussionmentioning
confidence: 98%
“…So that in one study, density of nerve bers stabilized at 3 months after sciatic nerve transection, but myelination was still increasing at 12 months [72]. Other studies have shown that myelination of nerve bers is not complete until 12 weeks after denervation [73]. Since the expression of S100 protein re ects the degree of myelination of nerve bers and the rate of S100 immune reactions is related to the thickness of the myelin sheath of Schwann cells [62].…”
Section: Discussionmentioning
confidence: 99%